2014
DOI: 10.1002/path.4435
|View full text |Cite
|
Sign up to set email alerts
|

Altered α‐defensin 5 expression in cervical squamocolumnar junction: implication in the formation of a viral/tumour‐permissive microenvironment

Abstract: Human papillomavirus (HPV) infection, particularly type 16, is causally associated with cancer of the uterine cervix, which mainly develops at the squamocolumnar (SC) junction. The progression of cervical HPV infections into (pre)neoplastic lesions suggests that viral antigens are not adequately recognized by innate immunity or presented to the adaptive immune system. Members of the defensin family have recently been found to inhibit viral and bacterial pathogens, to stimulate the migration of immune cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…New data suggest that cervical carcinoma originates at cells of the squamocolumnar junction (57). Recent evidence for reduced HD5 expression at these sites could render them more permissive to HPV infection (58). Moreover, ␣-defensins are known to act as cytokines and chemokines, and immune responses to HPV at these sites could be attenuated (6,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…New data suggest that cervical carcinoma originates at cells of the squamocolumnar junction (57). Recent evidence for reduced HD5 expression at these sites could render them more permissive to HPV infection (58). Moreover, ␣-defensins are known to act as cytokines and chemokines, and immune responses to HPV at these sites could be attenuated (6,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…HD5 is expressed in the ectocervix but not in the squamocolumnar junction or endocervix. It is possible that the absence of HD5 at this site allows for more HPV infection and therefore a greater possibility of cervical cancer progression (11). However, the squamocolumnar junction is also thought to be more permissive to HPV infection due to a surfaceexposed population of stem cells (13).…”
Section: ␣-Defensin Immunomodulatory Activity May Be More Important Tmentioning
confidence: 99%
“…Thus, direct antiviral activity in vivo is plausible. In the case of HPV, there has been interest in examining HD5 expression in cervical tissue, the site of HPV infection that leads to cancer (11). More than 90% of high-grade cervical intraepithelial neoplasias are thought to be due to HPV infection of a population of cells at the squamocolumnar junction, the region between the ectocervix and endocervix (12).…”
Section: ␣-Defensin Immunomodulatory Activity May Be More Important Tmentioning
confidence: 99%
“…These observations suggest that defensins play a role in the local immune response to HPV. In addition, Hubert et al (28) noted a regional disparity in the expression of human ␣-defensin 5, which was readily detectable in ectocervical, vaginal, and vulvar neoplasia but nearly absent from the cervical squamocolumnar junction, and suggested that this absence of ␣-defensin 5 may contribute to the unique susceptibility of the squamocolumnar junction to HPV infection and progressive disease.…”
Section: Hpv Infection and Disease Progressionmentioning
confidence: 99%
“…Defensins can block HPV infection (25,26) and potentially influence adaptive immunity by recruiting immune cells (27,28). Greater expression of ␤-defensins has been reported in HPV-associated genital warts than in uninfected tissue (29) and in anal intraepithelial neoplasia than in nonlesional tissue in men who have sex with men (30).…”
Section: Hpv Infection and Disease Progressionmentioning
confidence: 99%